Analysis of Costs and Benefits in Rehabilitation. Final Report - Rutgers, The State Univ., New Brunswick, NJ. Bureau of Economic Research; Berkowitz, Monroe; Rutgers, The State Univ., New Brunswick, NJ. Bureau of Economic Research ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
This report suggests feasible alternatives to the present methods of calculating benefits and costs of the joint federal-state vocational rehabilitation program. "Summary and Guide to Reading This Report" (Monroe Berkowitz) appears first. Part I, Background, Theory and Models, includes "The Cost Benefit Tradition in Vocational Rehabilitation" (Edward Berkowitz), "Welfare Measurement for Benefit Cost Analysis" (Douglas Blair and William Milberg), "Benefit Cost Models" (Jack Worrall), and "Models Based on Individual Behavior" (Duncan Mann). Part II, Benefit Cost Analysis using R-300 Data, contains "The R-300 Data Set" (Ernest Gibbs and Anita Hall-Kane), "Simple Benefit Cost Ratios" (Ernest Gibbs), "Benefit Cost Ratios using Multivariate Analysis" (Ernest Gibbs), "Correcting for Zero Wages at Referral" (An1ta Hall-Kane), and "Inputting Benefits to Persons Closed Not Rehabilitated" (David Dean and Robert Dolan). In Part III, Activity at the State Level, the chapters are "Benefit Cost Analyses Conducted by State Agencies" (Frederick Collignon) and "Collection of Data by State Agencies" (Stanley Portny). Part IV, Using Augmented Data Bases, includes "Using a Better Measure for Services" (David Dean and Robert Dolan), "Using Better Measures of Disability Status" (David Dean and William Milberg), "A Mini-Data Link" (David Dean and Robert Dolan), and a conclusion by Monroe Berkowitz. (YLB)
Sponsoring Agency: Department of Education, Washington, DC. Office of Planning, Budget, and Evaluation.
Contract Number: 300-84-0259.
Educational level discussed: Postsecondary Education.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Vocational Education; Cost Effectiveness; Data Analysis; Databases; Disabilities; Federal Programs; Federal State Relationship; Models; Postsecondary Education; Secondary Education; State Programs; Vocational Education; Vocational Rehabilitation; Reports, Research; Collected Works, General